Simultaneous Discovery and Taxonomic Placement of New Extant and Fossil Genera of Herbertiinae (Hymenoptera: Chalcidoidea: Pteromalidae). Issue 5 (5th September 2018) - Burks, Roger A; Krogmann, Lars; Heraty, John M
Abstract: Two new genera and species of Pteromalidae (Hymenoptera: Chalcidoidea) are described: the extant Exolabrum vannoorti n. gen., n. sp., from West Coast Fossil Park in South Africa, and Versolabrum coriaceum n. gen., n. sp. from Eocene Baltic amber. These are described in the previously monogeneric subfamily Herbertiinae based on the features of the labrum, subforaminal bridge, and fore leg. V. coriaceum is the first known fossil species of Herbertiinae, establishing this subfamily as having a minimum age in the Eocene Epoch, estimated age at 36.7–48.5 million years old.